1994
DOI: 10.1103/physrevlett.73.1865
|View full text |Cite
|
Sign up to set email alerts
|

Optical Conductivity of Insulating Al-Based Alloys: Comparison of Quasiperiodic and Periodic Systems

Abstract: We report on the optical conductivity of the structurally ordered icosahedral quasicrystal A17QPd2QRe IQ and the crystal A12Ru obtained from the reflectance measured over a wide frequency range. Our results show that both the crystal and the quasicrystal are semiconductors and have quite similar band structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 17 publications
2
53
1
Order By: Relevance
“…3,9 The estimated values of Born effective charges, comparable to those of typical ionic insulators, are very much larger than the static ionic charges, which previous calculation 2 has shown to be negligible. In this paper, we report the first-principles calculation of the zone-center phonon frequencies, the Born effective charges, and the dielectric tensor of Al 2 Ru.…”
Section: 78mentioning
confidence: 83%
See 1 more Smart Citation
“…3,9 The estimated values of Born effective charges, comparable to those of typical ionic insulators, are very much larger than the static ionic charges, which previous calculation 2 has shown to be negligible. In this paper, we report the first-principles calculation of the zone-center phonon frequencies, the Born effective charges, and the dielectric tensor of Al 2 Ru.…”
Section: 78mentioning
confidence: 83%
“…Because of its relatively simple crystal structure, it has been suggested 2,3 that investigation of Al 2 Ru can contribute to the understanding of the pseudogap in the electronic density of states observed in quasicrystals. From first-principles calculations of the bandstructure and charge density performed using linear-muffin-tin-orbitals (LMTO) in the atomic sphere approximation, 2 it has been shown that the fundamental gap results from the hybridization of sp(Al) and d(Ru) states.…”
mentioning
confidence: 99%
“…12,13) They possess the orthorhombic TiSi 2 structure, which has the space group Fddd with 24 atoms per unit cell. Basov et al 14) observed that the Al 2 Ru is infrared active, indicating the presence of a gap. Mandrus et al 15) reported the temperature dependence of the thermoelectric properties of the Al 2 Ru.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33] A universal experimental relation ϳ␥ Ϫ1/2 , discovered independently by Mizutani 32 and Rapp 33 for many i alloys, is indicative of the minimum of the DOS(E F ) in these alloys. The results of NMR, 34 -37 optical conductivity, [38][39][40][41][42][43] and photoconductivity 44 experiments were interpreted in terms of the pseudogap in the DOS(E F ) in the i alloys.…”
Section: Introductionmentioning
confidence: 99%